2008
DOI: 10.1146/annurev.anthro.37.081407.085230
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproductive Technologies and Culture Change

Abstract: In 1978, the world's first "test-tube" baby was born via in vitro fertilization (IVF). The past 30 years have seen the rapid evolution of many other assisted reproductive technologies (ARTs)-some are simple variants of IVF, whereas others bridge the fields of assisted reproduction and human genomics. As ARTs have evolved over time, so have social, cultural, legal, and ethical responses to them. Indeed, ARTs are a key symbol of our times, representing the growing prominence of biotechnologies in the configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(139 citation statements)
references
References 138 publications
4
121
0
14
Order By: Relevance
“…Other studies found that African and Arab women were not considered ''real'' women unless they had children, and were at a higher risk for domestic abuse. 9,[36][37][38] In Western biomedical models of treatment, the woman's body becomes the primary focus of infertility treatment, regardless of the physiologic cause of infertility, 3,39,40 highlighting the fact that Western culture is not exempt from the female-focused bias in infertility and assisted reproductive technology. Given these findings, it is possible that the greater use of CAM among our non-Western female participants was influenced by culturally based beliefs that they were responsible for infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies found that African and Arab women were not considered ''real'' women unless they had children, and were at a higher risk for domestic abuse. 9,[36][37][38] In Western biomedical models of treatment, the woman's body becomes the primary focus of infertility treatment, regardless of the physiologic cause of infertility, 3,39,40 highlighting the fact that Western culture is not exempt from the female-focused bias in infertility and assisted reproductive technology. Given these findings, it is possible that the greater use of CAM among our non-Western female participants was influenced by culturally based beliefs that they were responsible for infertility.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is now well established that culture and religion strongly influence one's understanding and experience of infertility, treatment options, and potential childlessness. 2,3 Many cultures also have well-established traditional healing methods for infertility that diverge from the Western biomedical model. [4][5][6] There remains a dearth of research exploring the experiences of non-Western immigrants who are pursuing fertility treatment in their new countries of residence.…”
mentioning
confidence: 99%
“…Certainly, the reproductive technologies have played a pivotal role in this transition, in that becoming a (biological) parent has become (seemingly) more feasible for many couples. But as documented by a large, and ever growing, body of ethnographic research, these 'global technologies' are not practiced in cultural voids, but rather are tailored according to the social, legal, economic, religious, and moral conditions of the various terrains in which they are placed at the service of creating 'local babies' (see Inhorn and Birenbaum-Carmeli, 2008). However, while the regulations and frameworks around these technologies have diverged almost endlessly, the experiences of women and men undergoing them in different global locations have proven to be surprisingly similar and familiar.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…Il faut en outre ajouter que certaines techniques, telles que la fécondation in vitro, ont significativement transformé la représentation et la signification des processus procréatifs, ainsi que nous le développerons plus loin. 4 Pour ce type de synthèse, voir notamment Thompson (2005), Franklin (2013a) et Inhorn et Birenhaum-Carmeli (2008).…”
Section: Les Apports Féministesunclassified